2016
DOI: 10.1002/pd.4781
|View full text |Cite
|
Sign up to set email alerts
|

Non‐invasive prenatal diagnosis of Duchenne and Becker muscular dystrophies by relative haplotype dosage

Abstract: ObjectiveDevelopment of an accurate and affordable test for the non‐invasive prenatal diagnosis of Duchenne and Becker muscular dystrophies (DMD/BMD) to implement in clinical practice.MethodCell‐free DNA was extracted from maternal blood and prepared for massively parallel sequencing on an Illumina MiSeq by targeted capture enrichment of single nucleotide polymorphisms (SNPs) across the dystrophin gene on chromosome X. Sequencing data were analysed by relative haplotype dosage.ResultsSeven healthy pregnant don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
70
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 40 publications
(95 reference statements)
1
70
0
1
Order By: Relevance
“…In this study, all 17 fetuses were accurately diagnosed as normal, carrier or affected using haplotype-based NIPD. This study and previous works of NIPD for DMD showed a high degree of accuracy compared with the invasive diagnosis results, as shown in Table 4 [11][12][13][14]. We also reviewed NIPD for other monogenic disorders [15].…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…In this study, all 17 fetuses were accurately diagnosed as normal, carrier or affected using haplotype-based NIPD. This study and previous works of NIPD for DMD showed a high degree of accuracy compared with the invasive diagnosis results, as shown in Table 4 [11][12][13][14]. We also reviewed NIPD for other monogenic disorders [15].…”
Section: Discussionsupporting
confidence: 56%
“…Currently, the position of the recombination event was confirmed by comparing the haplotypes of the proband and the CVS, or by bi-direcional (i.e. 5'to 3'and 3'to 5') evaluation of recombination sites in RHDO analysis [16]. We precisely assessed the position of the combination site to support a correct diagnosis, demonstrating the robustness of the haplotype-based approach.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Non-invasive prenatal testing for DMD is likely to become clinically available, allowing earlier identification of affected fetuses in women without a family history of DMD. 126 …”
Section: Discussionmentioning
confidence: 99%
“…Circulating nucleic acids can be analyzed at higher genomic coverage but this is to likely remain prohibitively expensive, does not overcome the problem of maternal cell‐free DNA background contamination, and requires complicated bioinformatics . For example, cffDNA from a pregnant woman could be sequenced to a depth of 195 × which provided a high positive predictive value and could detect fetal de novo mutations (including BRAF which encodes a proto‐oncogene).…”
Section: Introductionmentioning
confidence: 99%